The Effect of HRE-Regulated VEGF Expression and Transfection on Neural Stem Cells in Rats - Dou, Bo; Zheng, Xiangrong; Tan, Danfeng; Yin, Xixi (Frontiers in Cell and Developmental Biology, 2020)
Abstract Objective: To investigate whether hypoxia-responsive element (HRE) can enhance the expression of VEGF gene under hypoxic conditions and find a safe and efficient gene therapy for hypoxic-ischemic brain damage. Methods: Two recombinant lentiviral vectors pGC-FU-VEGF165 and 9HRE-pGC-FU-VEGF165 carrying VEGF165 gene were constructed and transfected into NSCs respectively. The transfected NSCs were divided into 7 groups. Fluorescence microscopy and flow cytometry were used to detect the efficiency of infection. The RT-PCR method was used to detect the expression level of VEGF gene in transgenic NSCs. Western-blot and Elisa methods were used to detect the expression level of transfected secretory VEGF protein. The MTT method was used to detect the proliferative activity of transfected NSCs. The comparison among groups was performed by the one-way ANOVA and LSD test. Results: According to the results of the flow cytometry, the cell transfection rate of Group A was about 50%; the cell transfection rates of Group B1 and Group D was about 0.49%.The results of RT-PCR and Western-blot showed that the expression of VEGFmRNA and corresponding proteins in Groups B2, B3 and B4 was significantly higher than Group A (P <0.05), and the expression of VEGFmRNA in Group B was increased with the prolonged length of hypoxia (P <0.05).The results of MTT showed no differences between Group C and Group D in the proliferative activity (P <0.05). The cell proliferative activity in Group A and Group B2 was higher than Group C and Group D (P <0.05). The cell proliferative activity in Group B2 was higher than Group A (P <0.05). Conclusions: NSCs-VEGF genetically engineered stem cells can secrete active VEGF protein and promote the proliferation of neural stem cells. Under hypoxia, HRE promoters can enhance the expression of VEGF gene. With the change of the length of hypoxia, HRE can regulate the expression level of VEGF.